Osteocytic vinculin controls bone mass by modulating Mef2c-driven sclerostin expression in mice - Yishu Wang; Jianmei Huang; Sixiong Lin; Lei Qin; Dingyu Hao; Peijun Zhang; Shaochuan Huo; Xuenong Zou; Di Chen; Guozhi Xiao (Bone Research)
Abstract The focal adhesion (FA) is the structural basis of the cell-extracellular matrix crosstalk and plays important roles in control of organ formation and function. Here we show that expression of FA protein vinculin is dramatically reduced in osteocytes in patients with aging-related osteoporosis. Vinculin loss severely impaired osteocyte adhesion and dendrite formation. Deleting vinculin using the mouse 10-kb Dmp1-Cre transgenic mice causes dramatic bone loss in the weight-bearing long bones and spine, but not in the skull, in both young and aged mice by impairing osteoblast formation and function without markedly affecting bone resorption. Vinculin loss impairs the anabolic response of skeleton to mechanical loading in mice. Vinculin knockdown increases, while vinculin overexpression decreases, sclerostin expression in osteocytes without impacting expression of Mef2c, a major transcriptional regulator of the Sost gene, which encodes sclerostin. Vinculin interacts with Mef2c and retains the latter in the cytoplasm. Thus, vinculin loss enhances Mef2c nuclear translocation and binding to the Sost enhancer ECR5 to promote sclerostin expression in osteocytes and reduces bone formation. Consistent with this notion, deleting Sost expression in osteocytes reverses the osteopenic phenotypes caused by vinculin loss in mice. Finally, we find that estrogen is a novel regulator of vinculin expression in osteocytes and that vinculin-deficient mice are resistant to ovariectomy-induced bone loss. Thus, we demonstrate a novel mechanism through which vinculin inhibits the Mef2c-driven sclerostin expression in osteocytes to promote bone formation.